PENGARUH PRAKTIK PENGAJARAN (MICROTEACHING) DAN MOTIVASI MENGAJAR TERHADAP KESIAPAN MENGAJAR - Handrianty Luqmana; Gimin; RM Riadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of Teaching Practice (Microteaching) and Teaching Motivation on Teaching Readiness among students of the Economics Education Study Program at Universitas Riau. The background of this research is the low level of teaching readiness among students when they are required to engage in direct teaching practice in schools. This research employed a quantitative approach with a total of 70 respondents from the 2021 and 2022 cohorts, selected using random sampling techniques. Data were collected through questionnaires and analyzed using classical assumption tests, multiple linear regression, t-tests, and F-tests. The findings reveal that teaching practice (microteaching) has a partial effect on teaching readiness with a significance value of 0.003, while teaching motivation also has a partial effect with a significance value of 0.002. Simultaneously, teaching practice and teaching motivation significantly affect teaching readiness. The coefficient of determination (R²) was 0.441, indicating that 44.1% of teaching readiness is explained by these two variables. These results suggest that effective teaching practice (microteaching) and strong teaching motivation can enhance the readiness of Economics Education students at Universitas Riau in preparing for their future role as teachers.